Intelligent temperature detection system based on“5G+AI” - Shan JIANG; Guocheng GONG; Tengyuan MA; Long XIAO (Dianxin kexue)
An intelligent temperature measurement solution based on “5G+AI” for the prevention and control of epidemic situation in COVID-19 was presented.Intelligent temperature measurement has a wide range of application scenarios in areas with dense traffic such as airports, railway stations and stations.A new AI temperature measurement architecture was proposed.The camera and infrared thermometer was used to measure temperature.The preprocessing module included image decoding, color space transformation, image correction and image normalization.Head detection model need to undergo off-line model training.Finally, through the temperature calculation module, the structured information was output.The development process of the model included data collection and annotation, model construction, model training, model optimization and model deployment.A comprehensive intelligent temperature measurement system was constructed, which integrated 5G temperature measurement hardware, OneNET access platform, monitoring application platform and mobile App.Finally, “5G+AI” intelligent temperature measurement products were successfully deployed in many cities and different application scenarios across the country.